Uncovering risk and protective factors towards bullying perpetration among adolescents in 15 countries/regions: the multilevel insights from SSES 2023 - Jinpeng Niu (International Journal of Adolescence and Youth)
Employing a two-level hierarchical linear modelling (HLM) analysis, the present study investigated risk and protective factors towards adolescent bullying perpetration in 15 countries/regions (N = 64,213), based on the 2023 Survey on Social and Emotional Skills (SSES) dataset. The findings indicated that (a) for individual factors, bullying perpetration is positively linked to academic anxiety and disruptive behaviours but negatively linked to life satisfaction and growth mindset and is more prevalent among boys; (b) for family factors, bullying perpetration is positively related to socioeconomic status (SES) but has no association with parent engagement in school; and (c) for school factors, bullying perpetration is positively related to gender-based violence and student population of low SES, but negatively related to school belonging, teacher–student relations, and school’s offer of extra-curricular activities. As well, significant interactions have been reported. Generally, this study reveals the diversity and complexity of factors on bullying perpetration among adolescents.